Impact of Extracurricular and Co-curricular Activities on Students’ Motivation toward Learning Science: A Gender-Based Analysis - Lamsal, Umanath (Bagiswori Journal, 2026)
The study investigated how Structured Extracurricular Activities (ECA) and Co-curricular Activities (CCA) programs affected the secondary level students’ motivation toward learning science on the basis of gender. The study employed a quasi-experimental study which included a non equivalent control group design that did not receive equivalent treatment to test 136 students of Grade IX from two schools in Kathmandu Valley, Nepal. The experimental group (n = 70; 30 boys and 40 girls) participated in a structured 8-month ECA/CCA intervention comprising 12 science-based activities, while the control group (n = 66; 42 boys and 24 girls) followed the standard national science curriculum without any structured intervention. Pre-testing with the Science Motivation Questionnaire II (SMQ-II) which assesses five motivational subscales: Intrinsic Motivation, Self-Efficacy, Self-Determination, Grade Motivation, and Career Motivation, standardized both groups. The experimental group demonstrated a statistically significant boost in total science motivation when compared with the control group as evidenced by post-test results (t(134) = 4.18, p < 0.001, Cohen’s d = 0.74). The two-way ANOVA demonstrated a significant effect of ECA, CCA, (F(1,132) = 5.87, p = 0.017) which showed that female students in the experimental group achieved greater motivational improvement than male students. The structured ECA/CCA experiences led to the most significant improvements in Self-Efficacy and Career Motivation for female students, showing that this method effectively addresses science motivation gaps between genders. Secondary school science education benefits from experiential learning programs because they increase student motivation and help achieve gender balance in STEM disciplines.